Advanced practice nursing in the care of older adults - Kennedy-Malone, Laurie, 1957-; Duffy, Evelyn Groenke (Philadelphia, PA : F.A. Davis Company, 2023)
'Advanced Practice Nursing in the Care of Older Adults will serve as a guide for advanced practice nurses who are privileged to provide care to older adults. Designed as a text for students, as well as a reliable source of evidence-based practice for advanced practice nurses, this book contains information on healthy aging, comprehensive geriatric assessment, and common symptoms and illnesses that present in older adults. Given the complexity of prescribing for older adults taking multiple medications, a chapter on polypharmacy is included. The book concludes with a chapter on care delivery for patients with chronic illnesses who face end-of-life care'--
Changes with Aging -- Health Promotion -- Exercise in Older Adults -- Nutritional Support in the Older Adult -- Settings of Care -- Comprehensive Geriatric Assessment -- Symptoms and Syndromes -- Dermatologic Disorders -- Head, Neck, and Face Disorders -- Cardiovascular Disorders -- Respiratory Disorders -- Peripheral Vascular Disorders -- Gastrointestinal Disorders -- Urologic and Renal Disorders -- Gynecologic Disorders -- Musculoskeletal Disorders -- Central and Peripheral Nervous System Disorders -- Endocrine and Metabolic Disorders -- Hematologic Disorders -- Psychosocial Disorders -- Polypharmacy -- Chronic Illness and the APRN -- Palliative Care and End-of-Life Care.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 05, 2023).
OCLC control number change
Keywords: Geriatric nursing -- Methods; Palliative treatment; Geriatric Nursing -- methods; Advanced Practice Nursing; Palliative Care; Geriatric Assessment